2009
DOI: 10.1007/s11259-009-9220-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Immunmodulatory effects of levamisole and vitamin E on Immunity and some blood parameters in newborn Jersey calves

Abstract: The immunmodulatory effects of dl-alpha tocopherol (vitamin E) and levamisole on the immune system and some blood parameters of newborn Jersey calves were investigated with the present study. Treatment groups 1, 2 and 3 were injected 13,3 ml isotonic saline solution (0,9% NaCl), 3 mg/kg levamisole HCl and 2000 IU vitamin E weekly, starting at birth until the age of two weeks. Average serum IgM levels of the control, levamisole and vitamin E calves were 111,7 +/- 9,3 mg/100 ml, 251,9 +/- 27,6 mg/100 ml, 202,2 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
6
7
2
Order By: Relevance
“…According to the result in table 1 we found that in group of LMS, WBC decreased after 21 day but was not statistically significant. This result was similar to those of Pekmezci and Cakiroglu (2009), Shah et al (2011) and Raina and Sachar (2014). In zinc group, the level of WBC decreased but was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the result in table 1 we found that in group of LMS, WBC decreased after 21 day but was not statistically significant. This result was similar to those of Pekmezci and Cakiroglu (2009), Shah et al (2011) and Raina and Sachar (2014). In zinc group, the level of WBC decreased but was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Level of WBC not changed AD3E group after 21 day. This result was similar to those of Pekmezci and Cakiroglu (2009).…”
Section: Discussionsupporting
confidence: 90%
“…The downregulating effect of GO on LEVA-induced serum IL-5 levels and gene expression in circulating leukocytes and the thymus is concordant with its recently reported anti-allergic effects (31). LEVA-induced IgG and IgM elevation provided evidence for the immunostimulatory effect of LEVA, and is in agreement with its effect on calves (32). The normalizing effects of GO on LEVA-induced IgG and IgM elevation indicated its immunomodulatory effect, and is in agreement with its lowering effect on IgG and IgM in human patients (33).…”
Section: A B C D E F G H I Discussionsupporting
confidence: 85%
“…Unfortunately, there is no such licensed or registered chemical or drug available in the market for chickens. Although levamisole was widely recognized and studied as a potential immune stimulant compound in many pharmacology text books and literatures (Ishikawa and Shimizu, 1983;Giambrone and Klesius, 1985;Bozić et al, 2006;Janjatović et al, 2008;Pekmezci and Cakiroglu, 2009), it did not demonstrate any immune enhancement effect in our study, no matter in SPF chickens or REV-induced immunosuppressed chickens (data are not included). Actually, there were some controversial reports on its immune enhancement (Van Der Maaten et al, 1983;Roth and Kaeberle, 1984;Purswell et al, 1998).…”
Section: Groupscontrasting
confidence: 54%